Pemberdayaan Masyarakat melalui Komunikasi Perubahan Sosial - Pramudya Falih Akmal (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Indonesia is one of the countries with the largest Muslim population, the mosque is a place intended to carry out worship and religious activities for Muslims. Activities in this community service journal are conducting community service activities which are located at the Al-Raudlah Mosque, Kasemen, Sawah Luhur, Serang. The service method used is the coordination of activities, implementation of activities and community empowerment, distribution of cleaning facilities, evaluation of activities, and preparation of reports. The problems found are the lack of public concern for the cleanliness of the worship environment, inadequate facilities and infrastructure, and security that has not been guaranteed. The implementation team hopes that in order to realize the image of the Al-Raudlah mosque, which is a place of worship and a center for Muslim religious activities, it will be kept clean and safe. Because the mosque environment has a function as a place to foster society to become a united people based on faith and piety. For this reason, through communication for social change, the implementing team hopes that the purpose of their service can be achieved, namely helping the community to be persuaded and aware of caring more in the future in maintaining the maintenance of the mosque environment.